The Effect of Repetitive Transcranial Magnetic Stimulation on Dysphagia After Stroke: A Systematic Review and Meta-Analysis - Yang, Weiwei; Cao, Xiongbin; Zhang, Xiaoyun; Wang, Xuebing; Li, Xiaowen; Huai, Yaping (Frontiers in Neuroscience, 2021)
Objective: The primary purpose of our study is to systemically evaluate the effect of repetitive transcranial magnetic stimulation (rTMS) on recovery of dysphagia after stroke. Search Methods: We searched randomized controlled trials (RCTs) and non-RCTs published by PubMed, the Cochrane Library, ScienceDirect, MEDLINE, and Web of Science from inception until April 24th, 2021. Language is limited as English. After screening and extracting the data, and evaluating the quality of the selected literature, we carried out the meta analysis with software RevMan 5.3, and summarize available evidence from non-RCTs. Results: Among 205 potentially relevant articles, 189 participants (from 10 RCTs) were recruited in the meta-analysis, and 6 non-RCTs were qualitatively described. The random-effects model analysis revealed a pooled effect size of SMD=0.65 (95% CI = 0.04 to 1.26, P=0.04), which indicated that rTMS therapy has a better effect than conventional therapy. However, the subgroup analysis showed that there was no significant difference between low-frequency and high-frequency groups. Even more surprisingly, there were no statistically significant differences between the two groups and the conventional training group in the subgroup analysis, but the combined effect was positive. Conclusion: Our study suggests that rTMS might be effective in treating patients with dysphagia after stroke